PEMANFAATAN INSENTIF PAJAK TERHADAP KEBERLANGSUNGAN USAHA PADA UMKM YANG TERDAMPAK COVID-19 - Emma Sukma Zulmida; Abdul Wahid Mahsuni; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The government's efforts in order to maintain business continuity while at the same time saving the national economy by implementing various socio-economic policy programs, one of which is the tax incentive policy contained in PMK Number 44/PMK.03/2020 concerning Tax Incentives for Taxpayers Affected by the Corona Virus Disease Pandemic. With the hope that tax incentives can be utilized and help UMKM actors affected by COVID-19 in maintaining business continuity.This study aims to determine the significant effect of partial use of tax incentives on the continuity of UMKM affected by COVID-19. With a registered UMKM population and taking advantage of tax incentives at KPP Pratama North Malang. The research method used is quantitative method and the data collection method is using a questionnaire. The data analysis method used simple regression analysis, and the tests used were descriptive statistical tests, data quality tests, classical assumption tests and hypothesis testing. The results of the study prove that the use of tax incentives has a partial positive effect on the sustainability of UMKM affected by COVID-19.Keywords: Tax Incentives, UMKM, Business Continuity, and Impact Covid-19.